Differential expression of Aquaporin 8 in human colonic epithelial cells and colorectal tumors - Fischer, Heléne (BioMed Central, 2001)
BACKGROUND: The gene expression pattern in tumor cells differs from that in corresponding normal cells. In order to identify differentially expressed genes in colorectal tumors and normal colorectal epithelium, a differential display experiment was used to compare RNA expression in normal and tumor tissue samples. RESULTS: One gene fragment was expressed only in normal tissue and not, or to a much lesser extent, in the adenomas, carcinomas and cancer cell lines. The isolated gene fragment was identical to Aquaporin 8 (AQP8), a water channel protein. In situ hybridization demonstrated that AQP8 was expressed in the cells facing the lumen in the normal colonic epithelium. CONCLUSION: Our result suggests that the expression of AQP8 is a marker of normal proliferating colonic epithelial cells and suggest these cells to be involved in fluid transport in the colon.